2015
DOI: 10.1016/j.toxrep.2014.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Green tea infusion improves cyclophosphamide-induced damage on male mice reproductive system

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 46 publications
(48 reference statements)
3
33
0
Order By: Relevance
“…The present study committed by other previous investigations, long-term treatment of MSG is correlated with several reversals in the nervous system [39][40], liver and kidneys [11,41] due to an elevation of ROS production [42]. Manuscript to be reviewed Also, Umukoro et al [43] demonstrated that orally administration of 500 mg/kg of MSG to mice elevated the malondialdehyde and diminished the GSH levels in brain tissue.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The present study committed by other previous investigations, long-term treatment of MSG is correlated with several reversals in the nervous system [39][40], liver and kidneys [11,41] due to an elevation of ROS production [42]. Manuscript to be reviewed Also, Umukoro et al [43] demonstrated that orally administration of 500 mg/kg of MSG to mice elevated the malondialdehyde and diminished the GSH levels in brain tissue.…”
Section: Discussionsupporting
confidence: 72%
“…The green tea extract (GTE) was processed as described before by Zanch et al [11]. The stock solution of MSG was provided by dissolving 60 g in 1000 mL of distilled water.…”
Section: Preparation Of Green Tea Extract Msg and Green Zno Np Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…Fahmy et al (2014) found a significant decrease in the percentage of sperm abnormalities in orally administrated soybean extracts. Zanchi et al (2015) demonstrated that polyphenols improved CP-induced damage on reproductive system, and its effect is probably due to high concentrations of catechins and antioxidant activity. According to the above results, it can be deduced that the combination of grape seed proanthocyanidins and siberian ginseng eleutherosides as well as green tea polyphenols and eleutherosides was able to weaken the reproductive toxicity induced by MTX.…”
Section: Discussionmentioning
confidence: 97%
“…Fahmy et al (2014) found a significant decrease in the percentage of sperm abnormalities in orally administrated soybean extracts. Zanchi et al (2015) Manuscript to be reviewed damage on reproductive system, and its effect is probably due to high concentrations of catechins and antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%